Fibration of idempotent measures - Radul , T. М. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 515.12We prove that the idempotent barycenter map restricted to the points with nontrivial fibers is a trivial fibration with Hilbert cube fibers whenever it is open.